Massive colonization by the solitary ascidian Microcosmus exasperatus Heller, 1878, on the sandy bottom of the Israeli littoral - Dan B. Golanski; Alona Nachmias; Gal Kahn; Amir Fireman; Ori Hepner Ucko; Noa Shenkar; Gitai Yahel (Aquatic Invasions, 2025)
The rapid increase in the arrival of tropical-origin species into the Levant region has dramatically changed local ecosystems. Non-indigenous species are known for their ability to utilize available ecological niches and in some events expand their non-native niche over time. Here, as an example of such expansion, we report on a massive colonization by the non-indigenous solitary ascidian, Microcosmus exasperatus (Heller, 1878), on soft bottoms along the Mediterranean coast of Israel. While this tropical-origin species is well-known for its ability to form dense aggregations on rocky substrates and artificial structures, only limited reports exist from soft-bottom habitats. In September 2022, a massive settlement of M. exasperatus was sighted on the sandy bottom (15–22 m depth) in front of Mikhmoret, Israel. M. exasperatus had settled on miniature “islets” of hard substrates, such as polychaete tubes, shells, or pebbles. By October, the population had reached a peak density, with a mean of 1.8±1.3 individuals m-2 (±95% confidence interval for the mean). Longshore visual surveys by towed divers revealed similar populations scattered along the central Israeli coast. Monthly compass surveys monitoring the population density, revealed a gradual population decline during late fall and winter, leading to a complete eradication in February 2023, probably due to a severe winter storm. No population was detectable throughout the spring but in August 2023 a few specimens were again detected on the sandy bottom, albeit at densities several orders of magnitude lower than the previous year. It is postulated that the ephemeral colonization of soft-bottom areas serves as “stepping stones” for the species’ dispersal into new habitats, potentially amplifying its invasive potential. Long-term monitoring across a more comprehensive depth range will reveal whether the observed massive colonization was a singular event or a recurring phenomenon that had previously remained unnoticed.